THE EFFECTIVENESS OF USING DESCRIBING PICTURE IN TEACHING SPEAKING - fathol ghafir rofiqi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
ABSTRACT: This research aimed to know about the use of describing pictures in teaching speaking to improve students’ speaking skill on eight grade class of junior high school students.This research implemented some aspects such observation, method, action and feedback of the result. Based on the research it improved the student’s speaking skill by using describing picture strategy as a media. This research used pre-test and post-test methods. The pre-test was done before implementing by using series of pictures as a media it was to measure student’s speaking ability at first. Mean while, the post-test was implemented as a form of describing pictures strategy in improving student’s speaking ability. It explains that describing picture has its own possition in teaching learning. It is becoming one of the best media in teaching speaking class. This research has already explained that describing picture technique is very beneficial in teaching speaking skill. It could give student’s speaking development. As the example, students can speak correctly for a real condition. It can also be seen in the result paired sample t-test that the describing picture method is receined as the good beneficial method in improving student’s speaking skill.Key words: Describing picture, speaking class, and junior high school.